High resolution analysis of the ν4, ν7 and ν12 vibrational bands of C2D4 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Fomchenko A. L. Anna Leonidovna; Zhang Fangce; Bauerecker Z. (S.) H. Zigurd (Sigurd) Hermann; Maul C. (Poster Session D, 2015)
Title screen